Keefektifan Bakteri Endofit dan Bakteri Perakaran Pemacu Pertumbuhan Tanaman dalam Menekan Penyakit Layu Bakteri pada Tomat - Zhenita Vinda Tri Handini; Abdjad Asih Nawangsih (Jurnal Fitopatologi Indonesia, 2014)
Bacterial wilt disease caused by Ralstonia solanacearum is an important disease on tomato. Endophytic bacteria and plant growth promoting rhizobacteria has been reported as potential biocontrol agent for many plant diseases. Research was conducted to determine the effectiveness of some isolates of endophytic bacteria (BC10, Bacillus amyloliquefaciens, dan Staphylococcus epidermidis BC4) and plant growth promoting rhizobacteria (Pseudomonas fluorescence RH4003, Bacillus subtilis AB89) as biocontrol agents for tomato wilt disease. Bacterial isolates was applied as soil drench on tomato seedling in single or combination treatments. Combination of P. fluorescens RH4003 and isolate BC10 (F1*BC10) enhanced the highest plant height, although plant dry mass among treatments was not significantly different. Single application of S. epidermidis BC4 was significantly suppressed disease incidence.